Kolerasi Sebaran Batubara dan Pemidelan Open Pit Pada Lapangan X, Tenggarong Seberang, Kabupaten Kutai Kartanegara, Kalimantan Timur - Oky Sugarbo; Helmi, Hurien (Kurvamas, 2025)
This community service activity is a one of the Tri Dharma activities of lecturers in college. On this occasion, service activities were carried out by modeling the distribution of coal and open pits modeling as well as mining simulation calculations for 3 months. The method that used in this service is a design and calculation method using surface and subsurface data. The solution from this service will be in the form of modeling and calculation of mining both overburden and coal, stripping ratio, and mine planning design for 3 months. With the coal distribution and open pit modeling, we can find out the configuration of the seam, the correlation between the seam, the shape and structure of the coal seam and the identification for production activities. The feasibility of mining of course pays attention to and uses the parameters of the distribution or geometry of the coal and the design of the open pit. On the other hand, the results of this service can provide understanding and planning about mining simulations for 3 months so that the number of mechanical tools (fleets) suitable for the mining process can be determined which will later have implications for mining optimization.